SOCIO-ECONOMIC IMPACT OF INSECURITY AND OIL BUNKERING ON FISHERIES PRODUCTION IN RIVER STATE (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
The Niger Delta region, particularly Rivers State, is a critical area for Nigeria’s fisheries production. However, the region faces significant challenges due to insecurity and illegal oil bunkering activities. This study aims to assess the socio-economic impact of these issues on fisheries production in Rivers State. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Data were collected from 300 fishermen across various communities in Rivers State between January and June 2024. Quantitative data were analyzed using SPSS version 25.0, while qualitative data were thematically analyzed to identify key patterns and themes. The findings revealed that insecurity and oil bunkering have severely impacted fisheries production. Approximately 65% of respondents reported a decline in fish catch over the past five years, attributing it to oil pollution and restricted access to fishing areas due to security concerns. The economic impact includes a significant reduction in income, with 70% of fishermen earning less than half of their previous income levels. Socially, the community has experienced increased poverty rates, disrupted livelihoods, and heightened tensions. The study underscores the urgent need for comprehensive policies and interventions to address the dual challenges of insecurity and oil bunkering. Enhancing security measures, promoting sustainable fishing practices, and providing alternative livelihoods are crucial steps towards mitigating the socio-economic impact on fisheries production in Rivers State.